Fruits and vegetables and the debate of the New Forest Code: Impact of income generation and quality of life of the Green Belt Community in the State of Maranhão (Research, Society and Development, 2021)
This research aimed to evaluate the income generation and quality of life of horticultural fruits of the São Luís-MA urban agglomeration micro-region. To answer our working hypothesis, we sought to understand what barriers are faced, whether they receive technical assistance, fiscal support and the use of new technologies. The preparation of the work was based on bibliographic reviews and environmental characterization of the Green Belt, was carried out through visits and application of questionnaires referring to the new forest code. The target audience was the fruit and vegetable growers who work in the area, which play a very important role for your city because a large part of the vegetables, fruit and poultry produced are consumed and sold at fairs in the region. As a result, it was possible to conclude that the community faces a serious problem with the lack of water, since this resource is essential for agricultural work. Family farming in the Green Belt shows itself to be in a vulnerable situation, seeking support and government investments. We had the opportunity to get to know the reality of these farmers, who still lack knowledge about the new forest code that aims to improve farmers. Based on the difficulties exposed in the research, it is recommended that the state and government are sensitized and help these producers to continue their work, providing support, technical assistance, and investments in new programs that help them and grow to improve their products. , their source of income, giving them a dignified and healthy life.